Implementasi Vector Error Correction Model dalam Menganalisis Hubungan Tingkat Kesejahteraan Petani Antar Subsektor - Zidni Permana Ardiansyah; Sri Harini; Juhari Juhari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the relationship between the level of farmers’ welfare between agricultural subsectors in Indonesia in the short and long term using the Vector Error Correction Model (VECM) approach. The data used includes the Farmer Exchange Rate (NTP) from five subsectors: Food, Hor ticulture, Plantations, Farms, and Fisheries. The results of the study show that there are differences in the relationship between subsectors in the short and long term. In the long term, Food NTP, Horti culture NTP, and Plantation NTP affect each other significantly, both positively and negatively, while Farms NTP and Fisheries NTP tend to have a more limited influence. On the other hand, short-term relationships are more influenced by NTP values from previous periods. The VECM model proved to be accurate in modeling the relationship between subsectors, with the Mean Absolute Percentage Error (MAPE) value of all subsectors being below 10%. In detail, MAPE for Food NTP is 2.18%, Horticulture NTP 4.18%, Plantation NTP 3.43%, Farms NTP 0.71%, and Fisheries NTP 0.86%. Thus, the VECM model is effectively used to analyze the dynamics of farmers’ welfare between subsectors in Indonesia.